Analysis of the type of cesarean scar pregnancy impacted on the effectiveness and safety of high intensity focused ultrasound combined with ultrasound-guided suction curettage treatment - Yan Peng; Yu Dai; Guiyuan Yu; Ping Jin (International Journal of Hyperthermia, 2022)
Objective To investigate the clinical efficacy and safety of high intensity focused ultrasound (HIFU) combined with ultrasound-guided suction curettage in patients with type I/II/III cesarean scar pregnancy (CSP).Methods A total of 153 patients with CSP were enrolled and classified according to the type of CSP. All of them were treated by HIFU combined with ultrasound-guided suction curettage. When active uterine bleeding was observed after curettage, a Foley balloon was used for hemostasis by compression. Baseline characteristics, technical parameters of HIFU, intraoperative blood loss in suction curettage, the time for serum β-HCG to return to normal levels, reproductive outcomes, and adverse effects were recorded and analyzed.Results 152 patients completed one session of HIFU combined with suction curettage except one patient transferred to surgery. Total energy used for ablation and the time for serum β-HCG return to normal level in type II and III were significantly higher than type I (p < .05). The treatment time and sonication time of HIFU in type III were significantly longer than type I (p < .05). Vaginal bleeding after curettage and the rate of using Foley catheter balloon in type III was larger than type I and II.Conclusions HIFU combined with ultrasound-guided suction curettage is a safe and effective treatment option for patients with type I/II/III CSP and desire for fertility. Patients with type III CSP were more dependent on Foley catheter balloon compression therapy than the other two types after HIFU combined with curettage.